1980
DOI: 10.1128/aem.39.1.13-16.1980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Sublethal Microwave Radiation and Conventional Heating on the Metabolic Activity of Staphylococcus aureus

Abstract: This study was conducted in an attempt to characterize some of the effects of sublethal microwave radiation on cells of Staphylococcus aureus. Cultures were exposed to microwave radiation for 10, 20, 30, and 40 s. The effects of a conventional heat treatment were also compared by placing flasks containing cultures in a boiling water bath for the amount of time required to reach temperatures equivalent to those found in cultures exposed to microwave radiation. Control, microwave-treated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 23 publications
3
51
0
1
Order By: Relevance
“…In other words, these results confirm the contributory nonthermal effects of microwaves resulting in enhanced inactivation of PME in orange juice as also observed in our previous study (Tajchakavit and Ramaswamy 1995). There (Dreyfuss and Chipley 1980;Khalil and Villota 1988). Some possible mechanisms for the nonthermal effects of microwaves which will most likely be explained as structural changes in a microscopic and molecular level, have been detailed in Olsen et ul.…”
Section: Microwave Inactivation Kineticssupporting
confidence: 90%
“…In other words, these results confirm the contributory nonthermal effects of microwaves resulting in enhanced inactivation of PME in orange juice as also observed in our previous study (Tajchakavit and Ramaswamy 1995). There (Dreyfuss and Chipley 1980;Khalil and Villota 1988). Some possible mechanisms for the nonthermal effects of microwaves which will most likely be explained as structural changes in a microscopic and molecular level, have been detailed in Olsen et ul.…”
Section: Microwave Inactivation Kineticssupporting
confidence: 90%
“…Meanwhile, other studies have reported their observations of non-thermal effect during microwave disinfection of microorganisms. They distinguished the non-thermal effect through examination of damaged cells (Campanha et al, 2007;Celandroni et al, 2004), distorted membrane structure and function (Persson, Salford, Brun, Eberhard, & Malmgren, 1992;Phelan, Neubauer, Timm, Neirenberg, & Lange, 1994), increased release of Ca 2 + , K + , DNA, dipicolinic acid and protein (Campanha et al, 2007;Celandroni et al, 2004;Vaid & Bishop, 1998) and altered the enzyme activities (Dreyfuss & Chipley, 1980) after microwave irradiation. Betti et al (2004) acknowledged the disruption of weak bonds in active protein forms, enhanced production of reactive oxygen species, and cell-signaling pathway interference to microwave non-thermal effects.…”
Section: Introductionmentioning
confidence: 99%
“…S5). High temperatures can cause denaturation and cell membrane damage [34], as well as alter enzymatic activities by disrupting weak bonds in active protein forms [35]. Moreover, MW irradiation exerts nonthermal effects on cell viability by interfering with cell signaling pathways, generating current within cells [36], and producing reactive oxygen species such as % OH [37].…”
Section: Bioaerosol Inactivation Performance By Mw Irradiationmentioning
confidence: 99%
“…Similar finding was observed by Wu et al [8] that the microwave-irradiated P. fluorescens cells apparently had damaged membrane envelope as observed in the SEM images. Previous researches showed that MW can alter enzymatic activities by disrupting weak bonds in active protein forms [38], and produce reactive oxygen species (such as % OH) [37], which was used to damage membrane envelope. The SEM images of E. coli cells before and after MW irradiation ( Fig.…”
Section: Bioaerosol Inactivation Performance By Mw Irradiationmentioning
confidence: 99%